APLIKASI PERHITUNGAN KAPASITOR SURFACE MOUNT DEVICE - Basorudin, Agus Irawan. (RJOCS (Riau Journal of Computer Science), 2017)
Calculate the capacitor by utilizing the technology will become more enjoyable and easier than counting capacitor using analog avometer. Calculating the capacitor will be easy fun and more interesting if we calculate it using the applications in the gadget that is growing rapidly at this time, especially android. Applications capacitor calculation Surface Mount Device android-based using java language and compiler software as the eclipse. There are three types of calculators capacitors, including two standard calculator ventax place code, calculator samsung alternate two code numbers and calculator samsung standard single place code. Design system used there are four, namely: Activity Diagram, Usecase Diagram, Sequence Diagram, and Deployment diagrams. The fourth component is part of the UML (Unified Modeling Language).